Protein Structure Prediction Methods and Protocols - Webster, David; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2000)
The deeper understanding of protein structure now emerging from cutting-edge research is not only illuminating evolutionary and biochemical mechanisms, but also promises enormous ramifications for molecular medicine, as well as for biotechnology, biophysics, biology, genetics, and other molecular sciences. In Protein Structure Prediction: Methods and Protocols, world-class investigators detail their most successful methods-and the theory behind them-for delineating the shape, form, and function of proteins. The protocols range from basic to advanced and include sequence alignment, the prediction of transmembrane protein structure, and the development of suitable folding potentials. There are also techniques for receptor site prediction, the identification of motifs and domains, the comparative modeling of proteins, the docking of peptides and ligands, and ab initio approaches to protein loop and side-chain prediction. To ensure robust and successful experimental results, each protocol contains step-by-step instructions, as well as tips on pitfalls to avoid and how procedures may be optimized for different systems. Comprehensive, accessible, and highly practical, Protein Structure Prediction: Methods and Protocols offers protein researchers, structural biologists, and other investigators a critical synthesis of the latest research results, as well as the vital guidance needed to understand the structure and interaction of proteins and peptides.
Multiple Sequence Alignment -- Protein Structure Comparison Using SAP -- Discovering Patterns Conserved in Sets of Unaligned Protein Sequences -- Identification of Domains from Protein Sequences -- Third Generation Prediction of Secondary Structures -- Comparative Protein Structure Modeling: Introduction and Practical Examples with Modeller -- A Practical Guide to Protein Structure Prediction -- Derivation and Testing Residue-Residue Mean-Force Potentials for Use in Protein Structure Prediction -- Genetic Algorithms and Protein Folding -- Scoring Functions for ab initio Protein Structure Prediction -- Ab Initio Loop Modeling and Its Application to Homology Modeling -- The Dead-End Elimination Theorem: -- Classification of Protein Folds -- Modeling Transmembrane Helix Bundles by Restrained MD Simulations -- Predictive Models of Protein-Active Sites -- Flexible Docking of Peptide Ligands to Proteins -- Geometrical Docking Algorithms: A Practical Approach -- Protein-Protein Docking: Generation and Filtering of Complexes.
Keywords: Biochemistry; Biochemistry, general